INSURANCE BUSINESS AS AN ELEMENT OF NATIONAL ECONOMY DEVELOPMENT - Yu. Т. Akhvlediany (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the role of insurance business in the development of national economy. It analyzes figures of insurance market, identifies the acute lines in its development and assesses the current condition of insurance industry. The author shows specific features of the effective Russian practice of protection of insurance service customers’ needs, explains legal innovations in protection of insured rights, puts forward recommendations dealing with high-quality risk management in conditions of digital economy and introduction of advanced system approaches for designing industry standards of insurance service customers’ protection with due regard to regional specificity of entities of the Russian Federation. Parameters of developing the business model of the insurance organization were identified. The author’s idea of the insurance innovation was offered and advantages of its use were demonstrated. On the basis of the analysis of the macro-economic situation on Russian regional insurance market the author assessed the level of insurance development in the territorial aspect. It was proposed to design regional insurance programs for the development of the insurance system, which could foster a rise in economic independence of regions and strengthening of finance market. Specific features of the insurance industry after joining the WTO were shown. The author came to the conclusion about the declining participation of foreign capital in insurers’ authorized capital, which proves a low interest in Russian market on the part of overseas investors. Priority goals aimed at insurance business development according to the Concept of risk-oriented approach, adopted by the Bank of Russia to regulate the Russian insurance sector were set.